Legal protection for farmers in the sale and purchase of paddy: The view of the MUI Babalan District and positive law (case study of Teluk Meku Village, Babalan District, Langkat Regency) - Fahmi, Muhammad Khairul; Iqbal, Muhammad Nur (Journal of Law Science, 2025)
The practice of buying and selling paddy in Teluk Meku Village is still conventional, with no written contracts, which weakens the bargaining position of farmers as prices are determined by middlemen and often fall below government standards. Non-cash payment systems, such as installments or deductions from future harvests, further increase farmers' dependence. From a sharia perspective, this practice does not fully align with the principles of justice, transparency, and honesty due to information imbalances and potential elements of gharar (uncertainty). In terms of positive law, Law No. 8 of 1999 on Consumer Protection guarantees farmers' rights to price and quality information, but its implementation remains weak due to limited government oversight and lack of socialization. This study uses a qualitative descriptive method with a case study approach through observation, interviews, and literature review. The results show that farmers suffer economic, legal, and sharia-related disadvantages due to limited market access and reliance on middlemen. The proposed solutions include forming cooperatives or farmer groups and strengthening government roles in price monitoring and educating farmers about their rights, aiming to create fairer transactions and reduce dependency on middlemen.